Increased Multidrug-Resistant Salmonella enterica I Serotype 4,[5],12:i:- Infections Associated with Pork, United States, 2009–2018 - Ian D. Plumb; Allison C. Brown; Erin K. Stokes; Jessica C. Chen; Heather Carleton; Beth Tolar; Preethi Sundararaman; Amy Saupe; Daniel C. Payne; Hazel J. Shah; Jason P. Folster; Cindy R. Friedman (Emerging Infectious Diseases, 2023)
Reports of Salmonella enterica I serotype 4,[5],12:i:- infections resistant to ampicillin, streptomycin, sulphamethoxazole, and tetracycline (ASSuT) have been increasing. We analyzed data from 5 national surveillance systems to describe the epidemiology, resistance traits, and genetics of infections with this Salmonella strain in the United States. We found ASSuT-resistant Salmonella 4,[5],12:i:- increased from 1.1% of Salmonella infections during 2009–2013 to 2.6% during 2014–2018; the proportion of Salmonella 4,[5],12:i:- isolates without this resistance pattern declined from 3.1% to 2.4% during the same timeframe. Among isolates sequenced during 2015–2018, a total of 69% were in the same phylogenetic clade. Within that clade, 77% of isolates had genetic determinants of ASSuT resistance, and 16% had genetic determinants of decreased susceptibility to ciprofloxacin, ceftriaxone, or azithromycin. Among outbreaks related to the multidrug-resistant clade, 63% were associated with pork consumption or contact with swine. Preventing Salmonella 4,[5],12:i:- carriage in swine would likely avert human infections.